2015
DOI: 10.12789/geocanj.2015.42.071
|View full text |Cite
|
Sign up to set email alerts
|

Igneous Rock Associations 18. Transition Metals in Oceanic Island Basalt: Relationships with the Mantle Components

Abstract: SUMMARYIncompatible elements and isotopic ratios identify three endmember mantle components in oceanic island basalt (OIB); EM1, EM2, and HIMU. We estimate compatible to mildly incompatible transition metal abundance trends (Ni, Co, Fe, Cu, Cr, V, Mn, Sc, and Zn) in 'primitive' basalt suites (Mg# = Mg/(Mg + 0.9*Fe) atomic = 0.72) from 12 end-member oceanic islands by regressing metals against Fe/Mg ratios in sample suites, and solving for concentrations at Mg/Fe = 1 (Mg# = 0.72). Using the transition metal est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
4
1
Order By: Relevance
“…In the case of the North Island Complex, it is unlikely that the parental magma was tholeiitic. The total alkali (Na 2 O+K 2 O wt%) content of the syenitic rocks of this study exceeds 11 wt%, the contemporaneous basaltic rocks reported from North Island and Silhouette are alkaline, and the most calcic plagioclase in the North Island gabbroic rocks is An37 which is common for the late crystallization stages of alkali basalt (Dickin et al, 1986;Greenough et al, 2005;Owen-Smith et al, 2013). Yet, the North Island Complex is metaluminous rather than peralkaline.…”
Section: Implications For the Tectonomagmatic Evolution Of The North ...contrasting
confidence: 51%
“…In the case of the North Island Complex, it is unlikely that the parental magma was tholeiitic. The total alkali (Na 2 O+K 2 O wt%) content of the syenitic rocks of this study exceeds 11 wt%, the contemporaneous basaltic rocks reported from North Island and Silhouette are alkaline, and the most calcic plagioclase in the North Island gabbroic rocks is An37 which is common for the late crystallization stages of alkali basalt (Dickin et al, 1986;Greenough et al, 2005;Owen-Smith et al, 2013). Yet, the North Island Complex is metaluminous rather than peralkaline.…”
Section: Implications For the Tectonomagmatic Evolution Of The North ...contrasting
confidence: 51%
“…The total alkalis versus silica diagram ( Figure 42; see List of Figures), higher Nb/Y ratios ( Figure 43), and steeper slopes of Wells Gray sideromelane on chondrite-normalized rare earth element (REE) diagrams (Figures 48 and 49) confirm that, for samples analyzed in this study, those from Wells Gray are more alkaline than those from Helgafell. Sideromelane analyses from the two Helgafell outcrops appear to have distinguishable characteristics with those low in the stratigraphic section showing subtly higher Nb/Y ratios ( Figure 43) consistent with higher percentages of melting (Condie, 2003;Floyd & Winchester, 1975;Greenough & MacKenzie, 2015;Greenough & Ya'acoby, 2013) as well as subtly lower Zr/TiO 2 ( Figure 43) indicative of slightly less differentiation (Hastie et al, 2007;Motoki et al, 2015;Murphy, 2007). The eruption that produced the unit may have been precipitated by the arrival of a new batch of magma to the magma chamber.…”
Section: Sideromelane Compositionsmentioning
confidence: 93%
“…Any two samples plotting close together on a MDS diagram have highly correlated element concentrations. The spread of geochemical analyses along the X and Y axes of MDS diagrams are thought to reflect the dominant processes that affected the samples; variation along dimension 1 should reflect the more dominant process (Greenough et al, 2010;Greenough & MacKenzie, 2015;Greenough & Ya'acoby, 2013). Thus, the observation that palagonite and sideromelane from each locality plot at a common dimension 1 value (Figures 52 and 53; see…”
Section: Relict Sideromelane Signatures In Palagonitementioning
confidence: 99%
See 2 more Smart Citations